INCREASING PRODUCTION FROM OLD, ONSHORE OIL FIELDS, AZERBAIJAN- A CASE STUDY - Griffiths A.E.; Begliarbekov V.R.; Shakbazov M.A.; Sultanov P. (My University, 2001)
As part of an effort to try to halt the decline in onshore oil production and accelerate production from onshore fields in Azerbaijan, a World Bank-sponsored study of four fields was carried out: the Bibi-Eybat, Kala, Buzovni-Mashtagi and Zirya fields. The study integrated geoscience, engineering, economics and environmental issues. This paper concentrates on the determination of methods for increasing production rates and recovery. The characteristics of the subject fields are summarized and their current status described. Methods for improving oil production rates in the fields include: mechanical work-overs, artificial lift optimization, sand-control and changes to well completion practices. Our work indicates that production rates could be raised between two- and ten-fold through the application of modern oil-field practices, but financial constraints have prevented their widespread use. Well intervention techniques form the basis of several outline field development plans, described with the associated production forecasts. A brief review is made of possible exploration plays which exist in and around the subject fields.
Keywords: Azerbaijan; FSU; Pliocene; depleted reservoir; development; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен